2018
DOI: 10.1128/jcm.00777-18
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Revised Ceftaroline Disk Diffusion Breakpoints When Testing a Challenge Collection of Methicillin-Resistant Staphylococcus aureus Isolates

Abstract: We assessed ceftaroline disk diffusion breakpoints for Staphylococcus aureus when applying revised Clinical and Laboratory Standards Institute (CLSI) ceftaroline MIC breakpoints. Disk-MIC correlation was evaluated by testing a challenge collection (n = 158) of methicillin-resistant S. aureus (MRSA) isolates composed of 106 randomly selected isolates plus 52 isolates with decreased susceptibility to ceftaroline (MIC, 1 to 16 μg/ml).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…These results highlighted different interpretations of the two institutes. Results from both CLSI methods were comparable, as already showed by Sader et al [ 18 ], while EUCAST demonstrated higher differences between disk diffusion and MIC interpretations. Our data confirmed discrepancies in EUCAST disk diffusion assays compared to MIC determination (both with broth microdilution or a MIC test strip) as reported before [ 19 ], and further suggested the need of a revision of disk diffusion criteria.…”
Section: Resultssupporting
confidence: 82%
“…These results highlighted different interpretations of the two institutes. Results from both CLSI methods were comparable, as already showed by Sader et al [ 18 ], while EUCAST demonstrated higher differences between disk diffusion and MIC interpretations. Our data confirmed discrepancies in EUCAST disk diffusion assays compared to MIC determination (both with broth microdilution or a MIC test strip) as reported before [ 19 ], and further suggested the need of a revision of disk diffusion criteria.…”
Section: Resultssupporting
confidence: 82%
“…We found that 30% of the CF MRSA isolates we tested were CPT-resistant. Considering that CPT was FDA-approved in 2010 14,15,26,[52][53][54] , i.e. after the collection of these strains, these findings are worrisome.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CPT demonstrated a high clinical cure rate (>70%) in pneumonia caused by both MSSA and MRSA 13 . CPT is active against MRSA with reduced susceptibility to vancomycin (VAN), linezolid (LZD), and daptomycin (DAP) 14,15 . The Clinical and Laboratory Standards Institute (CLSI) has established CPT breakpoints of ≤1 mg/L for susceptible MRSA strains, 2 mg/L for intermediate strains, and ≥4 mg/L for resistant strains 16,17 .…”
mentioning
confidence: 99%
“…Although the data presented by Urban and Stone are of great interest [1], they do not include MRSA isolates from the USA, and do not evaluate the impact of recent breakpoint changes for ceftaroline in either the Clinical Laboratory Standard Institute (CLSI) or the US Committee on Antimicrobial Susceptibility Testing (USCAST) [3,4]. The evaluation of S. aureus isolates from different regions is important because it has been demonstrated that the in vitro activity of ceftaroline against MRSA varies based on the SCCmec clonal types that predominate in a particular geographic location [5].…”
mentioning
confidence: 99%